Rat Models of Periodontitis: A Focused Review on Ligature, Bacterial Inoculation, and LPS-Induced Approaches - Afifah Astarini; Debby Handayati Harahap; Ayeshah Rosdah (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Periodontitis is a common chronic inflammatory disease that leads to progressive destruction of the gingiva, periodontal ligament, and alveolar bone. This is due to a dysbiotic oral microbiome that triggers an exaggerated host immune response. Preclinical rat models are indispensable in periodontal research, allowing for controlled investigations of disease mechanisms and therapeutic interventions. Review: This review examines three widely used rat models of experimental periodontitis, including ligature-induced, oral bacterial inoculation, and lipopolysaccharide (LPS) injection. The ligature-induced model is favored for its rapid and reproducible induction of localized inflammation and bone loss, although mechanical trauma may confound the microbial effects. Oral inoculation with pathogens such as Porphyromonas gingivalis simulates natural infections and chronic progression, offering greater biological relevance. The LPS model provides a controlled inflammatory stimulus that facilitates the study of host immune pathways and cytokine expression; however, it lacks microbial complexity. Recent studies have explored the combination of ligature and LPS methods to synergistically intensify inflammation and bone loss, thereby improving model robustness for therapeutic evaluation. Conclusion: Each animal model offers specific benefits for studying periodontitis development and treatment. Although these models have certain limitations, ongoing improvements in research methods will increase their relevance to human health. Advances in technology, imaging, and microbiological techniques are expected to improve the accuracy and usefulness of these models. These developments will enhance our understanding of the disease and contribute to the discovery of more effective and targeted treatment options for periodontitis.